Methodological Pathways to Improvements of Evaluation Approaches: The Case of Irrigated Agriculture Performance Evaluation - Anne Chaponnière; Serge Marlet; Sylvain R. Perret; Gabrielle Bouleau; Abdelaziz Zaïri (The Evaluation Center at Western Michigan University, 2012)
Background:  Irrigated agriculture is often evaluated but few reviews of evaluation methodology adapted to this object are available in the literature. Besides, recommendations to improve evaluation in this field are lacking.   Purpose: The purpose of the paper is to contribute filling this gap.   Setting: Not applicable.   Intervention: Not applicable. Research Design: Not applicable.   Data Collection and Analysis: Desk review.   Findings: This review shows the evolution of evaluation methodology in the field of irrigated agriculture pointing out a trend towards more comprehensive methodologies. The review also suggests some methodological tools to improve evaluation process. Keywords: irrigated agriculture; evaluation methodology; plurality of evaluation; intended users; viewpoint